Wideband Dual-Element Antenna Array for MIMO Mobile Phone Applications - Yuanqiang Wang; Jie Yang; Shangfu Hao; Xiao Zhang (International Journal of Antennas and Propagation)
A printed dual-element antenna array for LTE MIMO mobile phone applications is presented in this paper. The two array elements are symmetrically placed with the same dimensions, and each of the them consists of a novel driven strip and a wandering shorting strip. The driven strip is a whole loop, which improves the impedance matching for the upper band. Therefore, the bandwidth coverage is expanded and the antenna size is minimized at the same time. In addition, thanks to the protruded ground on the ground plane, the antenna isolation between the two array elements is significantly enhanced. The proposed planar antenna array successfully covers the seven operating bands of GSM850/900/1800/1900/UMTS2100/LTE2300/2500, and the isolation is more than 10 dB. The prototype was fabricated and tested, with S parameters, efficiency, radiation patterns, envelop correlation coefficient (ECC), and ergodic capacity presented. From the measured results, it is indicated that the antenna array has excellent and reliable performances when it is applied in MIMO applications.